Exercise prescription and tailored physical activity intervention in onco‐hematology inpatients, a personalized bedside approach to improve clinical best practice. Issue 3 (18th March 2019) - Duregon, Federica; Gobbo, Stefano; Bullo, Valentina; Roma, Enrico; Vendramin, Barbara; Bergamo, Manuele; Bocalini, Danilo Sales; Di Blasio, Andrea; Cugusi, Lucia; Neunhaeuserer, Daniel; Bergamin, Marco; Ermolao, Andrea
Abstract: Therapy of hematological malignancies lasts for long periods implicating various complications. The chemotherapy induces fatigue and forces bed rest. These features strongly contribute to a general impairment of the physical efficiency. Oppositely, an increase of physical exercise can prevent or reduce this weakening. Few trials examined the efficacy of an exercise in onco‐hematological inpatients, during their hospitalization. Therefore, this study aimed to determine the feasibility of an inter‐hospital intervention and the beneficial role of a tailored exercise program in the maintenance of the physical function in onco‐hematological inpatients. The study included 42 patients, which were allocated in two groups. In the intervention group (IG) a tailored exercise protocol during patient's hospitalization was administered. Exercise protocol was focused on development of strength, balance control, and flexibility; sessions were directly performed in the patient's hospital room everyday for 15 to 30 minutes. Exercise was supervised by an exercise specialist and driven by a multimedia support. Control group (CG) remained physically inactive for all period of hospitalization. To examine the interaction between the two situations (T0 and T1 ) and the two groups (IG and CG) for all dependent variables, a 2 × 2 within–subjects contrasts model analysis of variance was applied. Within groups analysis displayed significant differences in grip and leg strength and in static balance control ( P < 0.05) with medium to very large effect size. Results from this investigation showed that a tailored exercise protocol administered to hospitalized onco‐hematological patients was feasible and efficient to promote the maintenance of their physical function, improving clinical best practice including exercise to the traditional treatment. Moreover, the magnitude of the difference between the IG and the CG underlined the importance to invite and stimulate patients to workout to preserve the physical function, counteracting side effects of chemotherapy treatments with a concurrent reduction in bed rest syndrome.